The Impact of Islamic Monetary Instruments on the MSMEs Financing in Indonesia - Mohammad Zen Nasrudin Fajri; Nahdiyah Istiqomah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
As a monetary authority, Bank Indonesia prioritizes open market operations as one of its policies in influencing financial stability. In open market operations, business actors use SBI and PUAB short-term financial instruments in conventional banking and SBIS and PUAS in Islamic banking. Both of these instruments have a role in transmitting monetary policy to the real sector. Monetary transmission can occur through credit lines and MSME financing. This study aims to analyze the effect of sharia monetary instruments on channeling funds to the MSME sector. The data used in this study comes from Bank Indonesia and OJK for the period January 2012 to December 2021. Data analysis uses the VAR/VECM model, the Impulse Response Function (IRF) technique and the Forecast Error Variance Decomposition (FEVD). The results of the analysis show that the SBIS and PLS variables have a significant effect on MSMEs financing. Meanwhile, the PUAS variable has no significant effect on MSMEs financing channel. Based on the FEVD results, the variables of sharia instruments contributed to the MSME variable by 45.67%, while for the MSME financing variable, the financing distribution itself was 54.33%.